Spirit-Led Formation: Pentecostal Pneumatology and Children’s Spirituality in the Digital Era - Didimus Sutanto B. Prasetya; Johnly Mewengkang; Gunawan (DIEGESIS: Jurnal Teologi Kharismatika, 2025)
This study explores how Pentecostal pneumatology provides a theological foundation for shaping children’s spirituality in the digital era. The research addresses the problem of spiritual superficiality among Generation Alpha, which grows up in a technology-saturated environment that both connects and distracts. Using a qualitative theological approach that integrates hermeneutic and grounded theory methods, this study analyzes biblical texts (Acts 2; Joel 2) and recent scholarly findings in Pentecostal and Christian education. The results show that the Holy Spirit continues to work powerfully in digital contexts, forming children as active participants in God’s redemptive mission. A Spirit-led transformative framework is proposed, encompassing experiential, relational, cognitive, ethical, and missional dimensions that guide Christian education and family discipleship. The study concludes that technology can serve as a sacred medium for faith formation when it is directed by the Holy Spirit and supported by a Spirit-centered pedagogy. Keywords: Christian education; digital culture; Pentecostal pneumatology; spiritual formation; spirituality of children Abstrak Penelitian ini bertujuan untuk mengkaji bagaimana pneumatologi Pentakosta memberikan dasar teologis untuk pembentukan spiritualitas anak di era digital. Permasalahan utama yang diangkat adalah meningkatnya kecenderungan superfisialitas iman di kalangan Generasi Alfa yang tumbuh dalam budaya digital yang sarat dengan konektivitas, namun sering kali miskin kedalaman rohani. Penelitian ini menggunakan pendekatan teologi kualitatif dengan metode hermeneutik dan grounded theory, yang menggabungkan kajian eksegesis terhadap teks biblika (Kisah Para Rasul 2 dan Yoel 2) dengan analisis kepustakaan atas penelitian-penelitian terkini dalam bidang teologi Pentakosta dan pendidikan Kristen. Hasil penelitian menunjukkan bahwa Roh Kudus tetap berkarya secara aktif dalam konteks digital, membentuk anak-anak sebagai peserta yang berdaya rohani dalam misi penebusan Allah. Melalui kerangka Spirit-Led Transformative Formation, ditemukan bahwa pembentukan spiritualitas anak dapat dikembangkan melalui lima dimensi, yaitu pengalaman, relasional, kognitif, etis, dan misioner. Dengan demikian, teknologi tidak harus dipandang sebagai ancaman bagi iman, tetapi dapat menjadi media kudus untuk pendidikan rohani apabila diarahkan oleh bimbingan Roh Kudus serta didukung oleh pendekatan pedagogis yang berpusat pada karya-Nya. Kata kunci: budaya digital; formasi rohani; pendidikan Kristen; pneumatologi Pentakosta; spiritualitas anak